Adjuvant Therapy of Pancreatic Cancer: Beyond Gemcitabine - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
There is no consensus on what constitutes “standard” adjuvant therapy for pancreatic cancer. This controversy derives from several studies, each fraught with its own limitations. Standards of care also vary somewhat on the geography as chemo-radiotherapy followed by chemotherapy or vice versa is considered the optimal therapy in North America (GITSG, RTOG) while chemotherapy alone is the current standard in Europe (ESPAC-1, CONKO, ESPAC-3). The high rate of locoregional failure following surgical resection for adenocarcinoma of the pancreas has made it clear that some form of adjuvant therapy should be considered in these patients. A phase II study was presented at the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium to assess the effect of the addition of algenpantucel-L immunotherapy to standard adjuvant therapy on survival in patients with resected pancreas cancer (Abstract #236). The author reviews the abstract in the context of our previous knowledge. Image: Hyperacute rejection and immunotherapeutic applications.